2018
DOI: 10.1007/s10802-017-0395-1
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Executive Control and Internalizing Symptoms in Elementary School

Abstract: Depression and anxiety are prevalent and impairing forms of psychopathology in children and adolescents. Deficits in early executive control (EC) may contribute to the development of these problems, but longitudinal studies with rigorous measurement across key developmental periods are limited. The current study examines EC in preschool as a predictor of subsequent depression and anxiety symptoms in elementary school in a community sample (N = 280). Child participants completed a battery of nine developmentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 74 publications
(101 reference statements)
0
48
0
2
Order By: Relevance
“…Ao prover algumas evidências de validade e dados normativos preliminares, o estudo contribui para instrumentalizar a área de avaliação de FE na infância, sobretudo na etapa pré-escolar (Barros & Hazin, 2013) e soma os seus esforços a estudos portugueses na área (e.g., Moura et al, 2013;Moura et al, 2017;Pinto, 2008;Ribeiro et al, 2012;Simões et al, 2016;Teixeira, 2012). Reconhecendo a associação e contribuição das FE para o comportamento, aprendizagem e saúde mental infantil (Dias et al, 2017;Nelson et al, 2018;Nesbitt et al, 2015;Seabra et al, 2014), além de seu comprometimento nos Transtornos do Neurodesenvolvimento (Kimhi et al, 2014;Pauli-Pott & Becker, 2011), é importante que profissionais nos contextos clínico e escolar considerem a avaliação precoce dessas habilidades, não só para fins diagnósticos, mas para mapeamento de áreas de dificuldade. Esse será o primeiro passo para o planeamento de programas de estimulação.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ao prover algumas evidências de validade e dados normativos preliminares, o estudo contribui para instrumentalizar a área de avaliação de FE na infância, sobretudo na etapa pré-escolar (Barros & Hazin, 2013) e soma os seus esforços a estudos portugueses na área (e.g., Moura et al, 2013;Moura et al, 2017;Pinto, 2008;Ribeiro et al, 2012;Simões et al, 2016;Teixeira, 2012). Reconhecendo a associação e contribuição das FE para o comportamento, aprendizagem e saúde mental infantil (Dias et al, 2017;Nelson et al, 2018;Nesbitt et al, 2015;Seabra et al, 2014), além de seu comprometimento nos Transtornos do Neurodesenvolvimento (Kimhi et al, 2014;Pauli-Pott & Becker, 2011), é importante que profissionais nos contextos clínico e escolar considerem a avaliação precoce dessas habilidades, não só para fins diagnósticos, mas para mapeamento de áreas de dificuldade. Esse será o primeiro passo para o planeamento de programas de estimulação.…”
Section: Discussionunclassified
“…Evidências também apontam que, no período pré-escolar, as FE estão associadas a índices de comportamento e saúde mental infantil (Dias, Trevisan, León, Prust, & Seabra, 2017) e podem predizer sintomas de ansiedade e depressão no 4º ano do Ensino Fundamental, ou seja, são fatores de risco para psicopatologia infantil (Nelson, Kidwell, Nelson, Tomaso, Hankey, & Espy, 2018). Ao lado disso, a literatura tem documentado evidências da contribuição das FE para a aprendizagem escolar, sobretudo medidas em termos de desempenho em leitura e matemática (Nesbitt et al, 2015;Seabra et al, 2014).…”
Section: Introductionunclassified
“…They reported that the children high in internalizing symptoms were rated as less impulsive and lower in attentional control than the control children, but similar with regard to inhibitory control. Finally, some recent longitudinal studies have found that preschool EF difficulties, especially in inhibition and flexibility, are related to internalizing symptoms in the elementary school years [37,38].…”
Section: Introductionmentioning
confidence: 96%
“…Although EF have been identified as an important predictor for learning and be havior outcomes (e.g., Dias, Prust, & Seabra, submitted;Nelson et al, 2018;Schoemaker et al, 2013), some studies also have highlighted the role of other abilities in its develop ment. It is the case of oral language (OL; Bishop, Nation, & Patterson, 2014;Gordon Pershey, 2014;Roello, Ferretti, Colonnello, & Levi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A recent metaanalysis (Schoemaker et al, 2013) shows a consistent relationship between EF, more specifically inhibition, and externalizing behavior prob lems in preschoolers. Regarding internalizing behavior problems, Nelson et al (2018) found that EF in preschool age can predict symptoms of depression and anxiety when children reach the 4 th grade. With a national sample, Dias, Trevisan, León, Prust, & Seabra (2017) found evidence of EF, mainly IC and CF, as predictors of ratings as emo tional symptoms (IC and CF), behavior problems (only IC), hyperactivity (IC and also WM), peer relationship problems (CF), and prosocial behavior (CF) in preschoolers.…”
Section: Introductionmentioning
confidence: 99%